2002
DOI: 10.1254/jjp.88.442
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase IV Inhibition Improves Impaired Glucose Tolerance in High-Fat Diet-Fed Rats: Study Using a Fischer 344 Rat Substrain Deficient in Its Enzyme Activity

Abstract: ABSTRACT-This study was performed to determine the effects of a high-fat diet on glucose metabolism after an oral glucose challenge in high-fat diet-fed dipeptidyl peptidase IV (DPP-IV) positive (+) and deficient (-) Fischer 344 (F344) rats and the effects of novel DPP-IV inhibitor NVP-DPP728 (1-{2-[(5-cyanopyridin-2-yl)amino]ethylamino}acetyl-2-cyano-(S)-pyrrolidine monohydrochloride salt) on glucose tolerance in high-fat diet-fed F344 rats. In DPP-IV(+) rats, a high-fat diet load caused impaired glucose tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 33 publications
5
25
0
Order By: Relevance
“…A single oral dose of 3, 10, and 30 mg/kg SHR117887 inhibited serum DPP-4 activity by 84%, 91%, and 93%, respectively, at 2 h postdose, reducing serum glucose AUC 0-120 min by 30.2%, 35.0%, and 40.6%, respectively. LAF237 showed a similar pharmacological effect to SHR117887, and these findings are consistent with the previous reports using other DPP-4 inhibitors in glucose-intolerant rodents, including high-fat-fed rats [26,28] , Zucker fatty rats [30,31] and mice [32] . These results suggest that SHR117887 improves glucose tolerance through the elevation of serum insulin and active GLP-1 levels via the inhibition of DPP-4 activity in normal and diabetic animal models, but the achievable glucose lowering effect seems to be correlated with the degree of insulin resistance in different animal models.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A single oral dose of 3, 10, and 30 mg/kg SHR117887 inhibited serum DPP-4 activity by 84%, 91%, and 93%, respectively, at 2 h postdose, reducing serum glucose AUC 0-120 min by 30.2%, 35.0%, and 40.6%, respectively. LAF237 showed a similar pharmacological effect to SHR117887, and these findings are consistent with the previous reports using other DPP-4 inhibitors in glucose-intolerant rodents, including high-fat-fed rats [26,28] , Zucker fatty rats [30,31] and mice [32] . These results suggest that SHR117887 improves glucose tolerance through the elevation of serum insulin and active GLP-1 levels via the inhibition of DPP-4 activity in normal and diabetic animal models, but the achievable glucose lowering effect seems to be correlated with the degree of insulin resistance in different animal models.…”
Section: Discussionsupporting
confidence: 91%
“…We therefore further investigated the acute pharmacological effect of SHR117887 in the DIO rat, a model with modest insulin resistance and glucose intolerance [28] . The minimum effective dose of SHR117887 to augment the peak value of active GLP-1 and GLP-1 AUC 0-60 min was 3 mg/kg, which is also the minimum effective dose to increase the insulin peak value in 15 min after glucose loading.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of DPP4 for glucose homeostasis is revealed in studies characterizing the phenotype of DPP4-deficient rodents. DPP4-deficient rats exhibit elevated levels of GLP1 and improved glucose tolerance (94), and DPP4-deficient mice exhibit increased levels of plasma GLP1 and GIP (95), enhanced insulin secretion, improved glucose tolerance, and resistance to diet-induced obesity.…”
Section: Glp1r Agonists and Treatment Of T2dmmentioning
confidence: 99%
“…This finding that over 95% of the degradation of GLP-1 is attributed to the action of DPP-IV led to an elevated interest in inhibition of this enzyme for the treatment of type 2 diabetes [15]. Some previous studies have shown that specific DPP-IV inhibition increased the half-life of total circulating GLP-1, decreased plasma glucose, and improved impaired glucose tolerance in animal and human experiments [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…There are several chemical compounds used in vitro and in animal models to inhibit DPP-IV activity, such as Val-pyrrolidide [17], NVP-DPP728 [18], Lys[Z(NO2)]-thiazolidide and Lys[Z(NO2)]-pyrrolidide [19]. However, such chemical compounds, which often have to be administered by injection, may result in side effects as chemical drugs often do.…”
Section: Introductionmentioning
confidence: 99%